1990
DOI: 10.1901/jeab.1990.53-219
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Choice in a Percentage‐reinforcement Procedure: Effects of Signal Condition and Terminal‐link Length

Abstract: Pigeons' choice between reliable (100%) and unreliable (50%) reinforcement was studied using a concurrent-chains procedure. Initial links were fixed-ratio 1 schedules, and terminal links were equal fixed-time schedules. The duration of the terminal links was varied across conditions. The terminal link on the reliable side always ended in food; the terminal link on the unreliable side ended with food 50% of the time and otherwise with blackout. Different stimuli present during the 50% terminal links signaled fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
196
6

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 109 publications
(228 citation statements)
references
References 21 publications
26
196
6
Order By: Relevance
“…This is interesting because increasing the ITI decreases the overall rate of reinforcement available on the 50% alternative more than it decreases the overall rate of reinforcement available on the 100% side. These results are consistent with previous results obtained by Spetch et al (1990) and Mazur (1989), in suggesting that the relative value of an alternative leading to probabilistic reward is not altered by the duration of the ITI when the stimulus conditions during the ITI differ from those present during the trial. At the same time, the duration of the ITI was not completely without effect on behavior, because rate of responding to the terminal-link stimuli associated with food on both sides was higher when the ITI was long than it was when the ITI was short.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is interesting because increasing the ITI decreases the overall rate of reinforcement available on the 50% alternative more than it decreases the overall rate of reinforcement available on the 100% side. These results are consistent with previous results obtained by Spetch et al (1990) and Mazur (1989), in suggesting that the relative value of an alternative leading to probabilistic reward is not altered by the duration of the ITI when the stimulus conditions during the ITI differ from those present during the trial. At the same time, the duration of the ITI was not completely without effect on behavior, because rate of responding to the terminal-link stimuli associated with food on both sides was higher when the ITI was long than it was when the ITI was short.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, increases in the ITI have been found to diminish human subjects' tendency to choose uncertain large rewards over certain small ones in a discrete-trials hypothetical gambling procedure (Rachlin et al, 1986). In the discrete-trial concurrent-chains procedure with signaled outcomes, Spetch et al (1990) found no consistent effect of ITI duration on choice between 100% and 50% reinforcement. However, their study manipulated ITI only in the context of short terminal-link durations, in which pigeons displayed preference for the 100% alternative.…”
mentioning
confidence: 93%
See 3 more Smart Citations